Belt and Road Initiative in Central Asia: Anticipating socioecological challenges from large-scale infrastructure in a global biodiversity hotspot - Foggin, J. M.; Lechner, A. M.; Emslie‐Smith, M.; Hughes, A. C.; Sternberg, T.; Dossani, R. (Conservation Letters, 2021)
Until recently, China's Belt and Road Initiative (BRI) has overlooked many of the social and environmental dimensions of its projects and actions in favor of more immediate economic and sociopolitical considerations. The main focus of investments under BRI has largely been to improve transport, telecommunication, and energy infrastructures. However, in Central Asia, biodiversity is not only foundational for the livelihoods and socioeconomic wellbeing of communities, it also shapes people's culture and identities. Furthermore, ecosystem services derived from functioning landscapes bring enormous benefit for millions of people downstream through integrated and transboundary water systems. Already under pressure from climate-induced melting of glaciers, the fate of ecologically important areas is considered in light of the potential harm arising from large-scale linear infrastructure projects and related investments under China-led BRI. Following review of some of the anticipated impacts of BRI on mountain environments and societies in the region, we highlight several emerging opportunities and then offer recommendations for development programs—aiming fundamentally to enhance the sustainability of BRI investments. Leveraging new opportunities to strengthen partner countries’ priority Sustainable Development Goals and enhancing their agency in the selection of collaborations and the standards to use in environmental impact and risk assessments are recommended.